Sleep Deprivation Aggravates Cognitive Impairment by the Alteration of Hippocampal Neuronal Activity and the Density of Dendritic Spine in Isoflurane-Exposed Mice - Zhang, Kai; Lian, Naqi; Ding, Ran; Guo, Cunle; Dong, Xi; Li, Yuanyuan; Wei, Sheng; Jiao, Qingyan; Yu, Yonghao; Shen, Hui (Frontiers in Behavioral Neuroscience, 2020)
Isoflurane contributes to cognitive deficits when used as a general anesthetic, and so does sleep deprivation (SD). Patients usually suffer from insomnia before operation due to anxiety, fear and other factors. It remains unclear whether preoperative sleep deprivation (SD) exacerbates cognitive impairment induced by isoflurane. In this study, we observed the effects of pre-treated 24h SD in adult isoflurane-exposed mice on the cognitive behaviors, the Ca2+signals of dorsal hippocampal CA1 (dCA1) neurons in vivo with fiber photometry and the density of dendritic spines in hippocampal neurons. Our results showed that in cognitive behavior tasks, short-term memory damages were more severe with SD followed by isoflurane exposure than that with SD or isoflurane exposure separately, and interestingly, severe long-term memory deficits were induced only by SD followed by isoflurane exposure. Only the treatment of SD followed by isoflurane exposure could reversibly decrease the amplitude of Ca2+signals when mice were freely moving and increase the duration of Ca2+signals during the long-term memory behavior test. The density of dendritic spines with both SD and isoflurane exposure was lower than with SD alone. This study suggests that sleep deprivation should be avoided preoperatively in patients undergoing elective surgery under isoflurane anesthesia.